Problems of defining financial-legal measures for environmental protection in polish law (Ius Novum, 2024)
Effective protection of environmental resources is not possible without the use of instruments typical of financial law. This requires the use of public funds from the State and local governments, which are collected and spent in the manner prescribed by law. The Environmental Protection Law regulates the various legal-financial instruments used to fulfil this protective purpose. It also contains a provision defining what financial-legal measures are in terms of this Act. However, the legal definition is formulated in a way that raises numerous drafting and interpretative doubts. This article aims to demonstrate the accuracy of the thesis that there are defects in the statutory definition of legal and financial measures for environmental protection.
Keywords: financial-legal measures, environmental protection, legal definition